Alat Bantu Komunikasi Terintegrasi bagi Penyandang Tuna Wicara Berbasis Sensor Gerak dan OpenWrt - I Wayan Pasek Suyadnya; I Putu Wijaya Adi Candra; Nyoman Agus Nugraha Ginarsa; I Made Suartika (Jurnal SPEKTRUM, 2018)
Speech disorder is an individual who has difficulty in communicating. Speech disorder people is using non-verbal communication or sign language to be able communicate with other individuals. INSERT (Integrated Speech Disorder Helper Tools) is a prototype created to help communicate for speech disorder people so that it can make easier in communicating for speech disorder people. This tool using motion sensors in the work, that will translate sign language used by speech disorder people to voice. By using a Wireless Router device based on OpenWrt operating system will be applied database system that allows for updates of sign language that can be recognized by the tool.